2003
DOI: 10.4141/a02-053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variety and maturity stage on chemical composition, carbohydrate and protein subfractions, in vitro rumen degradability and energy values of timothy and alfalfa

Abstract: [279][280][281][282][283][284][285][286][287][288][289][290]. The objective of this study was to investigate the effects of forage variety and stage of maturity on chemical composition, protein and carbohydrate subfractions, in vitro rumen degradability and energy content under the climatic conditions of western Canada. Two varieties of alfalfa (Medicago sativa L. cvs. Pioneer and Beaver) and timothy (Phleum pratense L. cvs. Climax and Joliette), grown at three locations in Saskatchewan (Canada), were cut at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
84
5
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 23 publications
21
84
5
1
Order By: Relevance
“…ADF content increased with maturation (P<0.05). The findings in this experiment are in agreement with those reported by Yu et al (2003), Sayan et al (2004), Dolezal and Skladanka (2008), Homolko et al (2008), Canbolat and Karaman (2009), Aksoy and Nursoy (2010), Pop et al (2010). ADF is composed of cellulose and lignin, and there is an inverse relationship between ADF and digestibility.…”
Section: Chemical Composition Of Alfalfasupporting
confidence: 83%
See 3 more Smart Citations
“…ADF content increased with maturation (P<0.05). The findings in this experiment are in agreement with those reported by Yu et al (2003), Sayan et al (2004), Dolezal and Skladanka (2008), Homolko et al (2008), Canbolat and Karaman (2009), Aksoy and Nursoy (2010), Pop et al (2010). ADF is composed of cellulose and lignin, and there is an inverse relationship between ADF and digestibility.…”
Section: Chemical Composition Of Alfalfasupporting
confidence: 83%
“…ME content decreased with maturation due to an increase in CS, ADF and NDF (P<0.05). Our findings support some researcher's reports Yu et al (2003), Polat et al (2007), Aksoy and Nursoy (2010) reported that hemicellulose, cellulose and lignin, which are important cell wall components of forage fiber, have a negative effect on digestibility and related with this on energy values. The highest value of average NEL was determined Weir et al (1960), Manga (1978), Yolcu et al (2000), Yu et al (2003), Sayan et al (2004), Cozzi et al (2005), Özyigit and Bilen (2006), Dolezal andSkladanka (2008) Homolko et al (2008), Canbolat and Karaman (2009), Aksoy and Nursoy (2010), Pop et al (2010) in some legumes.…”
Section: Chemical Composition Of Alfalfasupporting
confidence: 82%
See 2 more Smart Citations
“…The above results are in agreement with Koukolová et al (2004), whereas the effects of maturity on degradability characteristics were comparable with those found in forage by elizalde et al (1999) and Yu et al (2004). Differences in phenophases are related to cell wall structures, complexity and components such as phenolic acid and lignin concentrations (Yu et al, 2003(Yu et al, , 2004, which are of vital importance for the cell wall carbohydrate degradability (Jung and Allen, 1995). Significant differences (P < The effect of declining feed digestibility with increasing maturity, as demonstrated by Rinne et al (2002) and Jančík et al (2008), was clearly illustrated in the present study.…”
Section: Resultssupporting
confidence: 80%